(untitled) (Research, Society and Development, 2020)
The objective of this work was to evaluate the in vitro potential effect of extracts of amazonian bee propolis on the growth of Xanthomonas axonopodis pv. manihotis, causal agent of cassava bacteriosis. The propolis samples were collected in apiaries with hives inhabited by Apis mellifera L. (africanized) bees in the municipalities of Santa Izabel and Curuçá, in the state of Pará. The extracts were obtained from static maceration for 24 h with hexane solvents, ethyl acetate and 80% ethanol. The phenolic profiles of the samples were obtained by High Performance Liquid Chromatography/Diode Array Detection/Mass Spectrometry with Electrospray Ionization. The antibacterial activity was verified with the extracts in concentrations of 0.1; 0.2; 0.3 and 0.4%. The chemical analysis revealed the presence of kaempferol in the Santa Izabel-PA sample, gallic acid in the Curuçá-PA sample, and 3,4-dihydroxybenzoic in both samples. The 80% ethanolic extract of the bee propolis from Santa Izabel significantly reduced the growth of X. axonopodis pv. manihotis.